2009
DOI: 10.1111/j.1742-4658.2009.07374.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the shutoff and exonuclease protein from the oncogenic Kaposi’s sarcoma‐associated herpesvirus

Abstract: The Kaposi’s sarcoma‐associated herpesvirus protein SOX (shut off and exonuclease) and its Epstein–Barr virus homolog, BGLF5, are active during the early lytic phase and belong to the alkaline nuclease family. Both proteins have been shown to be bifunctional, being responsible for DNA maturation as well as host shutoff at the mRNA level. We present the crystal structure of SOX determined at 1.85 Å resolution. By modeling DNA binding, we have identified catalytic residues that explain the preferred 5′‐exonuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 49 publications
5
44
0
Order By: Relevance
“…We noted that Tyr-371 is conserved in pUL12 homologs in herpesviruses in all Herpesviridae subfamilies (5,13), suggesting that the exonuclease activity of herpesvirus pUL12 homologs may be regulated by phosphorylation of the conserved tyrosine residues. In support of this hypothesis as well as our conclusion, the crystal structures of the pUL12 homologs of EpsteinBarr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) revealed that the tyrosines that correspond to HSV-1 pUL12 Tyr-371 were located in linker regions close to the catalytic sites (38,39). Therefore, it is reasonable that structural change mediated by phosphorylation of these tyrosines affects the catalytic activities of the pUL12 homologs.…”
Section: Discussionsupporting
confidence: 62%
“…We noted that Tyr-371 is conserved in pUL12 homologs in herpesviruses in all Herpesviridae subfamilies (5,13), suggesting that the exonuclease activity of herpesvirus pUL12 homologs may be regulated by phosphorylation of the conserved tyrosine residues. In support of this hypothesis as well as our conclusion, the crystal structures of the pUL12 homologs of EpsteinBarr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) revealed that the tyrosines that correspond to HSV-1 pUL12 Tyr-371 were located in linker regions close to the catalytic sites (38,39). Therefore, it is reasonable that structural change mediated by phosphorylation of these tyrosines affects the catalytic activities of the pUL12 homologs.…”
Section: Discussionsupporting
confidence: 62%
“…1A) (23,29). These included two well-characterized mutations in invariant residues of conserved motif II (29), which, based on the structures of the Kaposi's sarcoma-associated herpesvirus (KSHV) and EBV orthologs, lie in the active site of the enzyme (30,31). Mutational analysis has demonstrated that the G336A/S338A double-substitution mutation eliminates detectable exo-and endonuclease activities of UL12 whereas the D340E substitution mutation disrupts only exonuclease activity (29).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of gammaherpesvirus-specific conserved surface areas on the exonuclease would speak against the involvement of cofactor(s). However, most mutations found in shutoff-defective SOX variants map to the surface of the protein instead of the conserved catalytic site (10,18). Thus, the contribution of cofactor binding to gammaherpesvirus AE-mediated shutoff remains to be assessed.…”
Section: Discussionmentioning
confidence: 99%